Design and Analysis of a Hemispherical Parallel Mechanism for Forearm–Wrist Rehabilitation - Shuang Li; Zhanli Wang; Zaixiang Pang; Moyao Gao; Zhifeng Duan (Applied Bionics and Biomechanics)
This paper presents a bionic cable-driven mechanism to simulate the motion of human wrist which is suitable for human forearm–wrist rehabilitation. It fulfills workspace of the human forearm–wrist and it can train the joint in active and passive. With three degrees of freedom, it completes the supination/pronation of the forearm, the radial/ulnar deviation, and flexion/extension of the wrist. In addition to the movement of single degree of freedom of the forearm–wrist, it can also complete circumduction of the wrist. The mechanism consists of revolving platform, parallel mechanism, supporting mechanism, and movable table. Especially, in the parallel mechanism, a spring is added between the fixed and moving platform, and the moving platform is designed in the shape of a hemispherical shell. Utilizing the resilient properties of the extension spring and the support of the hemispherical shell, the problem of slack in the cable is solved in this mechanism. Since the spring is a passive component and cannot be calculated directly, a method combining kinematics and statics is proposed to calculate the relationship between the pose of the moving platform and the cable. Meanwhile, the kinematics, statics, and workspace solution of the mechanism are derived. Then, the simulation results demonstrate the accurateness and feasibility of the inverse kinematics and workspace derivation of the mechanism. Finally, the experiments are analyzed to verify the mechanism suitable for forearm–wrist rehabilitation tasks.